Emerging Trends in Curriculum: The Australian Experience - McGaw, Barry (Journal of Christian education, 2012)
This article overviews the history and features of the development of an Australia-wide F-10 curriculum over the last two decades. The discussion is set in the context of international efforts to measure the quality of educational efforts, specifically through the PISA and IEA surveys. Special focus is given to how religious worldviews are dealt with in the Australian Curriculum.